Entre a miséria e o sol: absurdo e criação em Albert Camus - Araujo, Michelle Fernandes de (2017)
The present work is a study of the philosophy of Albert Camus that aims to understand what posture man can have in relation to his existence, when he faces the absurd. According to Camus, we must always understand “absurd” as the helplessness that man's rationality feels in the face of the silence of the world and its ills. This helplessness eventually generates the confrontation that can lead us to what the philosopher calls "suicide" – which will be the subject of his criticismo – or even the ultimate end, which will be the aesthetic creation as the reverse of suicide. Both possibilities appear as ways of dealing with the absence of meaning of the world, namely, the absurd itself. However, if suicide (physical or philosophical) do not response to the meaninglessness of the world, it is up to us to think, from this, if it is possible to establish an ethos, a mode of action, that takes the creation aesthetics as a paradigm. It would be concerns to man to assumes a creative attitude, though without hope and without resorting to ideas that could be considered totalizing (for example, the search for a certain ideal of truth, a truth, very important to metaphysics, that would make sense or explain life and the world, hiding or not dealing with the absurd). The present text follows, therefore, the philosophical movement of the absurd reasoning proposed by Camus, seeking to explain what consequences can be deduced from the absurd as rule of action. In order to comply with this objective, our analysis focused on two of his Works: The Myth of Sisyphus, which helps us to think to what extent suicide is not an outlet for the apparent lack of sense of the world; and The foreigner, where we can notice the absurd both from the literary and the existential point of view.